Principles and Success of Edupreneurship in the Al-Qur’an - Nia Juwita Purnika Sari; Anwar Dhobith; Bahctiar Annas; Dwi Wulan Sari (al-Afkar, Journal For Islamic Studies, 2024)
Unemployment and poverty occur due to the comparison of the number of jobs offered in all sectors, domestically and abroad which includes the industrial, mining, mining, transportation, apritourism and other sectors which are not balanced by the number of graduates or the supply of new workers produced at all levels of education both junior high school to university level. This gap between demand and supply of labor must be equipped with entrepreneurial skills so that after graduating from school or college they still earn an income. The purpose of this research is to know the principles of edupreneurship in the qur'an. This study uses a qualitative descriptive method with a library research approach. Discoveries regarding edupreneurship principles contained in the Qur'an, namely the principle of monotheism, the principle of halal, the principle of hard work, the principle of honesty and professionalism, the principle of creative innovation and the principle of trust. As well as success in edupreneurship including being a successful entrepreneur, daring to take risks, planning, and being responsible.